Prehistoric settlement in Ljubljana: an urban trading centre at the crossroads - Vojaković Petra (Arheološki vestnik, 2023)
The prehistoric settlement in the area of present-day Ljubljana, built at the crossroads of many important trade routes, had acted as a trading centre since the time of the Urnfield culture. Inhabited from the 13th to the 5th century BC, it experienced a drastic population decline from the middle of the 8th to the 7th century BC, as evidenced by a small number of contemporary graves. The internal layout of the settlement found at Tribuna (in the area of the Prule district) suggests a thoughtful and well-planned design of the prehistoric settlement space. The location of the acropolis on the strategically important castle hill and the “lower town” of Tribuna, inhabited by craftsmen and merchants, also reveal distinct early urban elements. Given the natural affordances of the wider area, a neighbourhood of workshops and warehouses could be expected near the Ljubljanica River, while the area of the present-day Poljane district, with its fertile eutric soil, might have served as arable land.